Thermodynamic and Structural Modelling of Non-Stoichiometric Ln-Doped UO2 Solid Solutions,Ln = La, Pr, Nd, Gd - Vinograd, Victor L.; Bukaemskiy, Andrey A.; Modolo, Giuseppe; Deissmann, Guido; Bosbach, Dirk (Frontiers in Chemistry, 2021)
Available data on the dependence of the equilibrium chemical potential of oxygen on degrees of doping, z, and non-stoichiometry, x, y, in U1-zLnzO2+0.5(x-y) fluorite solid solutions and data on the dependence of the lattice parameter, a, on the same variables are combined within a unified structural-thermodynamic model. The thermodynamic model fits experimental isotherms of the oxygen potential under the assumptions of a non-ideal mixing of the endmembers, UO2, UO2.5, UO1.5, LnO1.5 and Ln0.5U0.5O2, and of a significant reduction in the configurational entropy arising from short-range ordering (SRO) within cation-anion distributions. The structural model further investigates the SRO in terms of constraints on admissible values of cation coordination numbers and, building on these constraints, fits the lattice parameter as a function of z, y and x. Linking together the thermodynamic and structural models allows predicting the lattice parameter as a function of z, T and the oxygen partial pressure. The model elucidates contrasting structural and thermodynamic changes due to the doping with LaO1.5, on the one hand, and with NdO1.5 and GdO1.5, on the other hand. An increased oxidation resistance in the case of Gd and Nd is attributed to strain effects caused by the lattice contraction due to the doping and to an increased thermodynamic cost of a further contraction required by the oxidation.